Gang members and extremists in Switzerland: Similarities and differences - Haymoz, Sandrine (European journal of criminology, 2023)
Scholars rarely compare youth gangs members and extremists. Yet, studies of gangs can yield relevant information on extremist groups, and vice versa. This article compares youth gang members with left-wing, right-wing and Islamist extremists. The aims of this article are to determine the prevalence of gang members and extremists among young people in Switzerland, to determine the overlap, if any, between gang members and extremists, and to analyse the differences and similarities of individual characteristics among the gang members and extremists, their delinquency and victimization. Comparisons of such groups may provide important insights into the individual members of these groups. The similarities between gang members and extremists could give us information for the prevention programmes. The study was based on a self-report survey completed by 8317 students of non-compulsory school age (about 17 years old) and living in Switzerland. The results show greater numbers of young people affiliated with gangs (6.6 percent) and left-wing extremism (6.2 percent), and more similarities between the members of gangs and left-wing extremists, compared with the other forms of extremism.